Penyusunan dalam Capaian Strategi Pembelajaran Terencana - Aziz, Abdul; Ramadhani, Hardika; Bakar, Muhammad Abu; Nurzahro, Yufaida (Lembaga Yasin AlSys, 2023)
The purpose of this study was to evaluate the effectiveness of planned learning strategies at SDN Semanan 14 Petang school. This research uses descriptive qualitative research methods. Data collection through interviews and observations. The results showed that teacher competence has a significant effect on student learning outcomes with effective and planned learning, parental involvement is very supportive also in improving student learning outcomes. Because deliberate changes in behavior during teaching and learning activities are the goal of education. The results of teaching and learning activities that are in line with educational goals are known as learning outcomes. A planned learning strategy is a must to achieve learning objectives, that is, establishing a framework or planning a learning approach as a systematic way of delivering learning materials to learners to achieve their learning5objectives. By relying heavily on learning strategies, teachers can achieve learning goals effectively and efficiently. With a good1design learning3strategies can provide the achievement2of the expected1learning1objectives.